BOOK REVIEW. DISTOPIA - Nuriadi Nuriadi (Humaniora, 2015)
Robert Frost, one of the most prominent American poets of the mid-20th century, once stated that “literature is a performance in words” (Barnet et al., 1961: 1). The phrase “performance in words” specifically refers to the real significance of language in the presentation of a literary work. If there is no language, then there will be absolutely no literature or literary work. Language serves not only as a medium for the work’s existence but also for a work to be called a work of art. Related to this proposition, poetry as a literary genre certainly exists because of the language by which the poets or the authors pour out their artistic and creative craftmanship, and through which readers can really read, enjoy, and concretize the poets’ ideas and messages.